Instrumentation of dental implants: a literature review - Curylofo, Fabiana de Almeida [UNESP] (2013)
The aim of this study was to review the literature on the systems used to decontaminate the implant's surface. Different instruments have been proposed, but there is no agreement in the literature about which methods would be more efficient with no damage to the implant surface. It was reported the use of plastic, carbon fiber, stainless-steel and titanium curettes and also the use of other systems such as ultrasonic points with different tips, rubber cups and air abrasion. Literature review: In most of the studies, the injury caused on the titanium surface at the time of instrumentation was examined. In others, the cell adhesion on the titanium dental implants following instrumentation of the implant surface was observed. Moreover, to enhance cleaning around implants, ultrasonic systems were recently tested. Conclusion: Metal instruments can lead to major damage to implant surface, therefore, they are not indicated for decontamination of dental implants surfaces. Furthermore, non-metallic instruments, such as plastic curettes, rubber cups, air abrasion and some ultrasonic systems seem to be better choices to remove calculus and plaque of the sub- and supra-gingival peri-implant area. It is noteworthy that more studies evaluating the effects of these systems are required to establish best practices to be used in the treatment of patients with dental implants.